More Than Just Balance: How Work-Life Balance Shapes Quiet Quitting and Job Satisfaction in Indonesia's Private Business Sector - Muhammad Ikhsan Alif; Prasis Damai Nursyam Hamijaya; Luh Made Wisnu Satyaninggrat; Masayu Sitti Nur Syabina (Department of Management, Universitas PGRI Yogyakarta., 2026)
Purpose: Amidst the rapidly evolving work environment in the post-COVID-19 era, this study aims to examine the effect of work-life balance on quiet quitting and job satisfaction among private sector employees in Indonesia, drawing upon the Conservation of Resources (COR) theory. Methodology: This research employs an explanatory quantitative design utilizing purposive sampling. Primary data were collected through structured questionnaires distributed to 125 respondents who met the criteria as full-time employees within the private sector in Indonesia. The statistical analysis and hypothesis testing were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0 software. Findings: The analytical results demonstrate that both proposed hypotheses are empirically supported. Specifically, work-life balance exhibits a strong negative and significant effect on quiet quitting (β = -0.728; f² = 0.530; p < 0.001). Furthermore, it demonstrates a positive and highly significant effect on job satisfaction (β = 0.807; f² = 0.652; p < 0.001). Implications: These findings underscore the critical need for management to implement concrete work-life balance policies within private sector companies. Initiatives such as establishing clear boundaries on work communication outside working hours and developing employee energy recovery programs are essential to effectively suppress quiet quitting behaviors and foster higher job satisfaction. Originality: This research is among the initial studies to position work-life balance as a shared antecedent of quiet quitting and job satisfaction simultaneously among private sector employees in Indonesia, enriching the empirical application of COR theory.